COURSE REVIEW HORAY METHOD IN TEACHING SPEAKING - Masruddin Masruddin (Institut Agama Islam Negeri Palopo, 2019)
This research aims at finding out whether the use of course review horay method is effective or not to improve the students’ speaking skill at the eight grade students of SMP Negeri 14 Palopo. This research was conducted at SMP Negeri 14 Palopo. It applied a pre experimental method. The total number of population was 38 students from two classes in the eight grade students. This research used purposive sampling which the researcher took class VIIIA. In this research the researcher used one instrument consisted of speaking test. Speaking test was given in pretest and posttest. The result of research shows that the use of course review horay is effective in teaching speaking. It is supported by the mean score of posttest (8,55) which is higher than pretest namely (13,66). Then, the P value of t-test was 0.00. It means that there is significant difference between the pretest and posttest